1985
DOI: 10.1111/j.2042-7158.1985.tb03030.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid uptake and peripheral distribution of centrally acting drugs: Relation to lipid solubility

Abstract: In an anaesthetized dog model, serum kinetics and CSF entry were determined after i.v. administration of the following 8 drugs: salicylic acid (as acetylsalicylic acid), antipyrine, acetaminophen (paracetamol), lidocaine (lignocaine), trimipramine, amitriptyline, haloperidol, and imipramine. Kinetic variables were evaluated in relation to in-vitro lipophilicity, measured by the reverse-phase high-pressure liquid chromatographic (HPLC) retention index. After correction for individual values of serum binding (de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 27 publications
3
26
0
Order By: Relevance
“…Similarly, Pardridge has shown a correlation between lipophilicity and brain penetration of hormones [17]. Moreover, Ochs et al found that the rate of brain uptake of drugs was dependent on their lipophilicity [18]. The lipophilicity (log D) of salicylic acid, antipyrine, and amitriptyline was -0.9, 0.4, and 3.0, respectively, and the time required to reach the peak drug concentration in cerebrospinal fluid (CSF) after intravenous administration to dogs was 200, 34, and 4 min, respectively [18].…”
Section: Physicochemical Properties and Membrane Permeabilitymentioning
confidence: 96%
See 1 more Smart Citation
“…Similarly, Pardridge has shown a correlation between lipophilicity and brain penetration of hormones [17]. Moreover, Ochs et al found that the rate of brain uptake of drugs was dependent on their lipophilicity [18]. The lipophilicity (log D) of salicylic acid, antipyrine, and amitriptyline was -0.9, 0.4, and 3.0, respectively, and the time required to reach the peak drug concentration in cerebrospinal fluid (CSF) after intravenous administration to dogs was 200, 34, and 4 min, respectively [18].…”
Section: Physicochemical Properties and Membrane Permeabilitymentioning
confidence: 96%
“…Moreover, Ochs et al found that the rate of brain uptake of drugs was dependent on their lipophilicity [18]. The lipophilicity (log D) of salicylic acid, antipyrine, and amitriptyline was -0.9, 0.4, and 3.0, respectively, and the time required to reach the peak drug concentration in cerebrospinal fluid (CSF) after intravenous administration to dogs was 200, 34, and 4 min, respectively [18]. However, a linear relationship between lipophilicity and membrane permeability can only be expected within a certain range.…”
Section: Physicochemical Properties and Membrane Permeabilitymentioning
confidence: 98%
“…As with previous studies of diazepam in the same species [12], flurazepam had high metabolic clearance averaging 37 ml/min/kg, and a short elimination half-life of 2.3 h. Like other lipophilic compounds [11], flura zepam was extensively distributed, with a mean volume of distribution of almost 8 1/kg. The only metabolite of flurazepam detected in serum was desalkylflurazepam, also a principal metabolite of flurazepam in humans [1,2,20,21], Other identified metabolic products of flurazepam were not measured in dog serum.…”
Section: Discussionmentioning
confidence: 51%
“…This experimental model has been utilized in previous studies to eval uate the serum pharmacokinetics, as well as the rate and extent of CSF entry, of a num ber of drug classes including benzodiaze pines, tricyclic antidepressants, neuroleptics, analgesics and antiarrhythmics [11][12][13], It is possible that the use of general anesthesia, which is necessary to allow cannulation of the CSF and repeated sampling from this site, could have altered the metabolic clear ance of the compounds evaluated in this and previous studies [ 13]. However, it is unlikely that anesthesia influenced peripheral tissue distribution and CSF entry, since these pro cesses appear to be governed by passive dis tribution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation